The aesthetics of story-telling as a technology of the plausible - Eidinow, Esther; Ramirez, Rafael (Elsevier, 2016)
In this paper we argue that that which philosophers consider as being included in the domain of the aesthetic is a crucial aspect determining the plausibility of a narrative; that plausibility actually plays a more significant role than probability in many cognitive processes of deliberation and decision making; and that the aesthetics of story-telling is a technology of the plausible. We offer two case-studies, one an ancient account of deliberation and decision making, the other from a modern newspaper article, to illustrate our argument that the aesthetic is an essential element in various stages of the process of decision making, from determining what needs to be decided, through identifying the basis for decision making, to the act of decision making itself. In that context, we highlight the role of the aesthetic in the framing of future possibilities in the process of scenario planning. In conclusion, we propose that focusing on the aesthetics of story-telling as a technology to create and share plausibility is a useful way to analyse scenario stories in scenario-planning work; we hope that it may be a useful concept with which to develop further research in this area.